Opial type Lp-inequalities for fractional derivatives - G. A. Anastassiou; J. J. Koliha; J. Pecaric (International Journal of Mathematics and Mathematical Sciences)
This paper presents a class of Lp-type Opial inequalities for generalized fractional derivatives for integrable functions based on the results obtained earlier by the first author for continuous functions (1998). The novelty of our approach is the use of the index law for fractional derivatives in lieu of Taylor's formula, which enables us to relax restrictions on the orders of fractional derivatives.